EARNINGS MANAGEMENT ANALYSIS ON SERVICE INDUSTRIES THAT SUPPORT TOURISM SECTOR AFTER THE EARTHQUAKE OF LOMBOK AND PALU - Nina Karina Karim; Siti Atikah; Indria Puspitasari Lenap (Jurnal Riset Akuntansi, 2020)
Earnings management practices in corporate financial statement continues to be an issue of debate in the financial accounting realm. Earnings management is done by the management of a company for various reasons. Information disclosed in the financial statement ideally must reflect the condition and performance of a company. Extraordinary events such as natural disaster surely will affect the performance of a company that is impacted by the event. A decline in corporate financial performance will affect the corporate stakeholders. This research aims to detect earnings management practices that might be conducted by service companies that support tourism industries affected by the earthquake that occurred in Lombok and Palu. Using the equation formulated by Stubben (2009) to detect earnings management practices by observing the change in discretionary revenues, this research has found that the natural disaster that hit Lombok and Palu was not a powerful enough extraordinary event that might have driven the management to conduct earnings management practices.